'Unlocking circular economy for prevention of marine plastic pollution: An exploration of G20 policy and initiatives'. (1st January 2021) - Fadeeva, Zinaida; Van Berkel, Rene
Abstract: Marine plastic pollution (MPP) is an urgent environmental and socio-economic problem. MPP amounts to 300 million tons annually, originates largely from land-based sources and severely impacts marine ecosystem, harms livelihoods and causes costs for businesses and governments. Plastics permeate the whole width and depth of seas and oceans, near well-developed coastal zones and equally in remotest corners. This undermines economic and social value of the oceans, particularly in terms of fisheries productivity and tourism. The G20 members, responsible for about two-thirds of global plastic waste, recognize the problem and undertake preventive measures – individually and collectively. Yet, are there efficient, effective and sufficient given the urgency of MPP and the contribution of G20 countries. This article highlights existing policies and identifies further policy options using a custom framework for MPP policy that merges Circular Economy (CE) and life-cycle perspectives. Graphical abstract: Image 1 Highlights: Marine plastic pollution (MPP) is of urgent ecological, economic and social concern. MPP largely originates through 'leaks' from production and consumption on land. Circular economy (CE) provides framework for action to prevent MPP. Promising MPP policies exist across G20, but require scale, ambition and coherence.